Advances in Manufacturing II Volume 1 - Solutions for Industry 4.0 - Trojanowska, Justyna; Ciszak, Olaf; Machado, José Mendes; Pavlenko, Ivan (Lecture Notes in Mechanical Engineering,, 2019)
This book covers a variety of topics related to the Industry 4.0 concept, with a special emphasis on the efficiency of production processes and innovative solutions for smart factories. It describes tools supporting this concept in both the mechanical engineering and biomedical engineering field. The content is based on papers presented at the 6th International Scientific-Technical Conference MANUFACTURING 2019, held on 19-22 May 2019, in Poznan, Poland. Virtual reality, simulation of manufacturing systems, additive manufacturing, big data analysis, automation and application of artificial intelligence, as well as economic and social issues related to the integration of those technologies are just some of the topics discussed here. All in all, the book offers a timely and practice-oriented reference guide for researchers and practitioners, and is expected to foster better communication and closer cooperation between universities and their business and industrial partners.